The emergence of global Maoism : China's red evangelism and the Cambodian communist movement, 1949-1979 - Galway, Matthew (Ithaca: Cornell University Press, 2022)
"This book takes a genealogical approach to uncovering the processes whereby Maoism came into existence, how the Chinese Communist Party (CCP) actively exported it outside China, and the conditions of its emergence in Cambodian intellectual circles where it inspired the future leaders of the Communist Party of Kampuchea (CPK)"--
Discovering truth through practice: Mao Zedong thought conceived and implemented, 1927-1965 -- Transmitting Maoism: Mao's global revolution, 1965-1975 -- The origins of Cambodia's Maoist vision: revolutionary intellectuals and Maoism, 1949-1955 -- Integrating truth with concrete practice: intellectual adaptations of Maoism, 1955-1965 -- Like desiccated straw in the ricefields: practical and normative adaptations of Maoism, 1966-1975 -- We must combine theory and practice: the implementation of Cambodia's Maoist vision, 1975-1979
Includes bibliographical references (pag 273-309) and index.
Keywords: Communism and philosophy -- Cambodia; Communism and philosophy -- China; Communism -- Cambodia; Communism -- China